Stability results for the solutions of a certain third order nonlinear differential equation (2008)
The paper is concerned with the uniform asymptotic stability for all solutions of a third order nonlinear differential equation (1.1). Sufficient conditions under which all solutions x(t), its first and second derivatives tend to zero as t —∞ are given